(untitled) (BioLaw Journal - Rivista di BioDiritto, 2026)
This article investigates the epistemic role of science in shaping judicial reasoning on states’ environmental and climate obligations. It argues that scientific knowledge functions not merely as auxiliary evidence but as an epistemic infrastructure through which courts construct, interpret and enforce climate-related duties. By examining jurisprudence from the Inter-American and European human rights systems, alongside landmark national and international precedents, the study argues that courts progressively embed scientific consensus into legal argumentation. This process enables them to translate empirical findings – particularly those consolidated by the IPCC – into normative benchmarks for assessing state responsibility in environmental and climate matters.